Safety and efficacy of a novel double-lumen tracheal tube in neonates with RDS: A prospective cohort study - Li, Chuanfeng; Du, Yuxuan; Yang, Kaiting; Cao, Huiling; Yang, Hong; Zhang, ChunXiu; Li, Xiongbin; Deng, Xingmei; Shi, Yuan (Frontiers in Pediatrics, 2022)
Background: The purpose of this study was to assess the safety and efficacy of a new double-lumen tracheal tube for neonates, with a conventional tracheal tube as a control. Method: Newborns with NRDS requiring endotracheal intubation admitted to the tertiary NICU of Qujing Maternal and Child Healthcare Hospital in Yunnan Province between March 2021 and May 2022 were enrolled in this prospective cohort study. Outcome indicators related to effectiveness included mainly the number of intubations, duration of ventilation, duration of oxygenation, and length of stay; safety indicators included any clinical adverse effects during and after intubation. Appropriate stratified and subgroup analyses were performed according to the purpose of intubation, gestational age, and whether the drug was administered via endotracheal tube. Result: A total of 101 neonates were included and divided into two groups based on the choice of tracheal tube: the conventional and new tracheal tube groups. There was no statistical difference between the two groups in terms of adverse effects during and after intubation. In neonates who were mechanically ventilated without endotracheal surfactant therapy or newborns receiving InSurE technique, no significant differences were found between the two groups regarding any of the efficacy indicators. However, for neonates on invasive mechanical ventilation, the new tracheal tube allowed for a significant reduction in the duration of mechanical ventilation and total ventilation, when used as a route for endotracheal drug delivery. Further analysis was performed according to gestational age for newborns requiring intratracheal surfactant administration during mechanical ventilation, and the data showed that for preterm infants, the new tracheal tube not only shortened the duration of mechanical and total ventilation, but also demonstrated significant advantages in reducing the duration of oxygen therapy; however, there was no statistical difference in efficacy outcomes between the two groups in full-term infants. Conclusion: The efficacy and safety of this new tracheal tube are promising in neonates with NRDS, especially those requiring surfactant administration via a tracheal tube during mechanical ventilation. Given the limitations of this study, however, the clinical feasibility of this catheter needs to be further confirmed in prospective randomized trials with larger sample sizes.